Colon Interposition for Esophagus and Pyloric Antrum Strictures Caused by Caustic Agent Ingestion - Andry Irawan; Abdul Mughni Rozi (PT Kalbe Farma Tbk., 2019)
Swallowing irritating agent can cause chemical burn, which can develop complications such as stricture. Correctional procedures may cause further tissue damage with additional loss of function. Colon interposition is a therapeutic option for severe stricture cases. Menelan agen iritatif mengandung bahan kimia seperti asam atau basa dapat menyebabkan luka bakar kimiawi, pada beberapa kasus menyebabkan komplikasi striktur ringan hingga berat. Beberapa prosedur koreksi esofagus dapat menyebabkan kerusakan jaringan lebih lanjut dengan kehilangan fungsi. Interposisi colon merupakan pilihan terapi kasus striktur berat.